Viscoelastic properties and reinforcement of non-aggregated and aggregated nanocomposites. (6th June 2018) - Pirner, Daniela; Dulle, Martin; Förster, Stephan
Abstract: We investigate the properties of polymer nanocomposites consisting of narrow disperse spherical nanoparticles that are coated with narrow disperse polymers. These nanoparticles can be homogeneously dispersed in a polymer matrix. The structure of the polymer-coated nanoparticles was examined by using small angle X-ray scattering (SAXS) and transmission electron microscopy (TEM), and was related to the viscoelastic properties of the nanocomposites. We observe a systematic retardation of the polymer relaxation dynamics with increasing particle loading. Nanoparticle aggregation leading to the formation of chain-like structures causes a strong reinforcement effect. Graphical abstract: Image 1 Highlights: Nanoparticles coated with polymers at high grafting densities are fully miscible with polymer matrices in nanocomposites. The addition of nanoparticles retards the mobility of the polymer matrix chains, which increases the storage and loss moduli of the matrix. At lower grafting densities nanoparticles aggregate into chain-like structures, which leads to mechanical reinforcement.